Synthesis of ultrafine WC-10Co composite powders with carbon boat added and densification by sinter-HIP. (January 2017) - Yang, Qiumin; Yang, Jiangao; Yang, Hailin; Ni, Guohua; Ruan, Jianming
Abstract: WC-10Co composite powders without carbon deficient phase and free carbon could be synthesized by the method with carbon boat added in the reduction-carbonization process. The carbon boat in the furnace could balance the carbon activity spontaneously during the reduction-carbonization process, which made the carbon diffusion rate match with the carbonization rate. The mean particle size of the composite powders was 175 nm with partly faceted, slightly elongated shape. The present method has distinct advantage of lower reaction temperature and shorter holding time over the previous methods. Furthermore, consolidation of the ultrafine W C -10Co composite powders in a sinter-HIP furnace was investigated. After consolidated, the WC-10Co alloy from the powders synthesized with the carbon boat added exhibited two-phase alloy with a homogeneous fine-grain microstructure and good combined mechanical properties of hardness 1985 ± 50 HV and fracture toughness 10.2 MPa·m 1/2 . Highlights: WC-10Co composite powders were synthesized by the method with carbon boat added. The carbon boat could adjust the carbon activity spontaneously during the reduction-carbonization process. The carbon boat affected the microstructure and particle size of the composite powders.